Investigation of the genetic aetiology of Lewy body diseases with and without dementia - Wu, LY; Real, R; Martinez-Carrasco, A; Chia, R; Lawton, MA; Shoai, M; Bresner, C; Blauwendraat, C; Singleton, AB; Ryten, M; International Lewy Body Dementia Genomics Consortium; Scholz, SW; et al. (Oxford University Press, 2024)
Up to 80% of Parkinson's disease patients develop dementia, but time to dementia varies widely from motor symptom onset. Dementia with Lewy bodies presents with clinical features similar to Parkinson’s disease dementia, but cognitive impairment precedes or coincides with motor onset. It remains controversial whether dementia with Lewy bodies and Parkinson's disease dementia are distinct conditions or represent part of a disease spectrum. The biological mechanisms underlying disease heterogeneity, in particular the development of dementia, remain poorly understood, but will likely be the key to understanding disease pathways and, ultimately, therapy development. Previous genome-wide association studies in Parkinson's disease and dementia with Lewy bodies/Parkinson's disease dementia have identified risk loci differentiating patients from controls. We collated data for 7804 patients of European ancestry from Tracking Parkinson’s, The Oxford Discovery Cohort, and Accelerating Medicine Partnership—Parkinson's Disease Initiative. We conducted a discrete phenotype genome-wide association study comparing Lewy body diseases with and without dementia to decode disease heterogeneity by investigating the genetic drivers of dementia in Lewy body diseases. We found that risk allele rs429358 tagging APOEe4 increases the odds of developing dementia, and that rs7668531 near the MMRN1 and SNCA-AS1 genes and an intronic variant rs17442721 tagging LRRK2 G2019S on chromosome 12 are protective against dementia. These results should be validated in autopsy-confirmed cases in future studies.